2020
DOI: 10.3389/fphar.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Basic Fibroblast Growth Factor on Diabetic Nephropathy Through Remodeling Metabolic Phenotype and Suppressing Oxidative Stress in Mice

Abstract: Diabetic nephropathy is a common complication in diabetes, but still lack of effective therapeutic strategies. This study aimed to investigate the therapeutic effect of basic fibroblast growth factor (bFGF) in db/db mice with diabetic nephropathy and explore its possible metabolic mechanisms using a nuclear magnetic resonance-based metabolomic approach. We found that bFGF treatment significantly alleviate urinary albumin to creatinine ratio and renal fibrosis in db/db mice, suggesting a potential renal protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Apoptosis can promote tubular cell hypertrophy, glomerular basement membrane dilatation, and accumulation of extracellular matrix, which contribute to progressive tubulointerstitial fibrosis and glomerulosclerosi. Therefore, it is considered to be an important inducer of renal remodeling 8 . Furthermore, autophagy is negatively correlated with renal fibrosis including glomerular extracellular matrix accumulation and tubulointerstitial fibrosis 3 , 9 , 10 , while autophagy deficiency promotes the progression of glomerular lesions and tubulointerstitial damage 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis can promote tubular cell hypertrophy, glomerular basement membrane dilatation, and accumulation of extracellular matrix, which contribute to progressive tubulointerstitial fibrosis and glomerulosclerosi. Therefore, it is considered to be an important inducer of renal remodeling 8 . Furthermore, autophagy is negatively correlated with renal fibrosis including glomerular extracellular matrix accumulation and tubulointerstitial fibrosis 3 , 9 , 10 , while autophagy deficiency promotes the progression of glomerular lesions and tubulointerstitial damage 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Mice with fibroblast-specific disruption of the FGFR2 gene demonstrated decreased total collagen deposition, fibronectin, and alpha smooth muscle actin expression in an ischemia-reperfusion model [56,57]. On the other hand, treatment with bFGF alleviated oxidative stress and apoptosis in the kidney in db/db mice [58]. In a model of streptozotocin-induced diabetes in Sprague-Dawley rats, bFGF delayed the progression of diabetic nephropathy, possibly by inhibiting NF-κB and silencing of TGF-β1, MCP-1, IL-6, and IL-1β [59].…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with various studies that reported the factors secreted from MSC contain antioxidants as one of the predominant elements, which are included in CM and exert anti-oxidative effects in paracrine mechanisms [ 13 , 58 , 59 , 60 ]. In particular, numerous growth factors found in CM of human amnion tissue and AMSC [ 61 ] have been identified to function as antioxidants including insulin-like growth factor [ 62 ], platelet-derived growth factor [ 63 ], epidermal growth factor [ 64 ], hepatocyte growth factor [ 65 ] and fibroblast growth factor [ 66 ]. Moreover, pre- and post-IVC medium analysis revealed that the activities of SOD and catalase were higher in culture medium supplemented with AMSC-CM than the medium with ASC-CM ( Figure 5 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%